Black-headed Gulls wintering in Sulawesi (and notes on their occurrence elsewhere in the Indo-Australia region) - Argeloo, Marc (KUKILA, 1992)
The numbers and distribution are discussed of the Black-headed Gull Larus ridibundus as a wintering visitor in Indonesia and adjacent areas. The first observations during the 1950's were confined to the island of Borneo. Since the beginning of the 1960’s, more birds were observed at different sites, especially in the north and east. Most birds were in first winter plumage.